Reliability and validity of General Burnout Scale in multiple populations - Jin WANG; Xiaoman LIU; Yanyan SUN; Jianlin LOU; Fang YUAN; Daoyuan SUN; Ruijie LING; Dan YU; Shuang LI (环境与职业医学, 2023)
BackgroundAs one of the common tools for job burnout assessment, Maslach Burnout Inventory-General Survey (MBI-GS), its reliability and validity across different populations in China have not been examined yet.ObjectiveTo evaluate the reliability and validity of General Burnout Scale (GBS) by multiple occupational groups through the translation and preliminary test of MBI-GS.MethodsBased on the Special Project of Occupational Hazards in Key Populations led by the Institute of Occupational Health and Poison Control, China CDC, key occupational groups in five typical industries were selected by multi-stage stratified cluster sampling, including teachers, firefighters, manufacturing workers, medical staff, and traffic police. Confirmatory factor analysis (CFA) was used to evaluate the construct validity of GBS by single-factor, two-factor, and three-factor structure models. The model fitness was assessed by ratio of the chi-square statistic to the respective degrees of freedom (χ2/ν), root mean square error of approximation (RMSEA), goodness-of-fit index (GFI), comparative fit index (CFI), and parsimony-adjusted non-normed fit index (PNFI). Spearman correlation analysis was used to calculate the criterion validity of GBS with occupational stress, depressive symptoms, and sleep disorders. Cronbach's α coefficient and composite reliability (CR) coefficient were used to evaluate the internal consistency reliability of GBS.ResultsA total of 3485 subjects were surveyed in this study, 3375 valid questionnaires were recovered with a valid response rate of 96.84%. The results of CFA showed that in the adjusted three-factor structure model of GBS (exhaustion, cynicism, and professional efficacy), the χ2/ν < 4, the RMSEA ranged from 0.032 to 0.069, the GFI > 0.90, the CFI > 0.90, and the PNFI > 0.70, which illustrated a good fitness than that of the single- or the two-factor structure models in different occupational groups. The Spearman correlation analysis results showed that occupational stress, depressive symptoms, and sleep disorders were positively correlated with exhaustion and cynicism dimensions, and negatively correlated with professional efficacy dimension of the GBS, with the \begin{document}$ \left| r \right| $\end{document} ranging from 0.139 to 0.662 (P<0.05) in overall subjects. For traffic police and firefighters, professional efficacy was not correlated with depressive symptoms or sleep disorders (P>0.05). The Cronbach's α coefficients ranged from 0.819 to 0.899, and the CR values ranged from 0.941 to 0.978 in different occupational groups.ConclusionThe GBS shows high reliability and validity, as well as good application effects in different occupational groups.